Chronic Obstructive Pulmonary Disease is associated with risk of Chronic Kidney Disease: A Nationwide Case-Cohort Study - Chen, Chung-Yu (Sci Rep, 2016)
Patients with chronic obstructive pulmonary disease (COPD) and chronic kidney disease (CKD) share common risk factors. However, there is limited information about COPD and CKD. This is case-cohort study was carried out using the Taiwanese National Health Insurance Research Database to evaluate the correlation between COPD and CKD. We identified cases aged older than 40 years who had an inpatient hospitalization with a first-time COPD diagnosis between 1998 and 2008. Control were selected from hospitalized patients without COPD or CKD and were matched according to age, gender, and year of admission at a 2:1 ratio. Cox proportional hazards model was used to assess the association of CKD and COPD. The overall incidence of CKD was higher in the COPD group (470.9 per 10(4) person-years) than in the non-COPD group (287.52 per 10(4) person-years). The adjusted hazard ratio of case was 1.61 (P < 0.0001) times that of control. COPD was found to be associated with kidney disease from our follow-up. To detect CKD early, early diagnosis of CKD in patients with COPD and prompt initiation of monitoring and treatment are imperative.